An Empirical Analysis of Sell-through in a Fashion Setting - Juan Enrique Flores; Pol Boada; Philip Moscoso (International Journal of Supply Chain Management, 2014)
Sell-through is a widely used performance metric in retail supply chains, but limited empirical research exists about its validity for that purpose, given its dependence on many different variables. This study analyses to what extent sell-through is influenced by fixed store attributes (e.g. store size), and what impact on this metric operational management decisions (e.g. replenishment) have. Using data collected from a fashion retailer, a sales model was developed to estimate the statistical contribution of the different types of impacts to sell-through. Results of the study provided strong empirical evidence that fixed store attributes such as store size can impact significantly sell-through levels. Operational management decisions also have a statistically significant impact on sell-through, but to a much smaller extent. This makes sell-through more valuable for compare performance when fixed store attributes are not differential.